PENGARUH GAYA KEPEMIMPINAN (TRANSFORMASIONAL DAN TRANSAKSIONAL) DAN KEPUASAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) (STUDI KASUS PADA GEN Y) - Zuhrotul Ainy (Politeknik Negeri Lhokseumawe, 2022)
Abstract: Within a company, leaders can influence morale, job satisfaction, security, quality of work life, and especially the level of prestige of an organization. In addition, leaders also play a critical role in helping groups, organizations or communities to achieve goals. However, leadership abilities and skills in providing direction are important factors of manager effectiveness. The objectives to be achieved in this study are to identify and analyze the influence of transformational leadership style on Organizational citizenship behavior, to identify and analyze the effect of transactional leadership style on Organizational citizenship behavior, and to identify and analyze the effect of job satisfaction on Organizational citizenship behavior. Based on the calculation of multiple linear regression analysis, it can be seen from the results of the t test that has been done that X1 (Transformational Leadership Style) with Y (Organizational Citizenship Behavior) shows t count = -0.017. Because t count t table, namely -0.017 2.06, the effect of X1 (Transformational Leadership Style) on OCB is not significant. The t test between X2 (Transactional Leadership Style) and Y (Organizational Citizenship Behavior) shows t count = 0.404. While the t table is 2.06, the effect of X2 (Transactional Leadership Style) on OCB is not significant. The t test between X3 (Job Satisfaction) and Y (Organizational Citizenship Behavior) shows t count = 2.225. While t table is 2.06, the effect of X3 (Job Satisfaction) on OCB is significant, so it can be concluded that OCB can be significantly influenced by Job Satisfaction. From the test results above, it can be seen that only the variable X3 (Job Satisfaction) has a significant influence on Organizational Citizenship Behavior.Keywords : Transformational Leadership, Transactional Leadership, Job Satisfaction, OCB